If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + 16 + b = 18 + b Reorder the terms: 16 + 2a + b = 18 + b Add '-1b' to each side of the equation. 16 + 2a + b + -1b = 18 + b + -1b Combine like terms: b + -1b = 0 16 + 2a + 0 = 18 + b + -1b 16 + 2a = 18 + b + -1b Combine like terms: b + -1b = 0 16 + 2a = 18 + 0 16 + 2a = 18 Solving 16 + 2a = 18 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 2a = 18 + -16 Combine like terms: 16 + -16 = 0 0 + 2a = 18 + -16 2a = 18 + -16 Combine like terms: 18 + -16 = 2 2a = 2 Divide each side by '2'. a = 1 Simplifying a = 1
| 9x+26x^2=3 | | 6y-2=2y+7 | | 8+3x+x=20 | | 58474+46274= | | t=5(2)+3(4) | | 15-3x+2-8x=39 | | 58584839748375097+85574758475398= | | 7x-5y+(-3x+-4y)= | | M(m+2)=2 | | 5x-13=-25 | | 13y^2-4y-9=0 | | 4w=w-2 | | 13y^2-4y+9=0 | | x^2+y^2=4x-4y-6 | | 40+7x=0 | | 0.3*x+x^2=0.3x^3 | | (3c-2)(2c+5)=0 | | x^2+y^2-4x+4y+6=0 | | (45x^6)-(36y^2)-144=0 | | (45x^2)-(36x^2)-144=0 | | (36x^2)+(36x^2)-144=0 | | 4v-3=-5 | | (y^2-6)+(90)+(y+1)=180 | | 13x-10+12x=180 | | (10y^2)+(y^2-6)+(y+1)=180 | | 15(-1/6)n=(1/6)n-1 | | 2x-6x+42=0 | | (5y-5)=(2y+2) | | 5y-5=2y+2 | | x^2=6.3125 | | 4x-35+2x+3=x-19 | | x^2y^2-4x+2y-5=0 |